Attachment to place in advanced age: A study of the LiLACS NZ cohort. (July 2017) - Wiles, Janine L.; Rolleston, Anna; Pillai, Avinesh; Broad, Joanna; Teh, Ruth; Gott, Merryn; Kerse, Ngaire
Abstract: An extensive body of research theorises that attachment to place is positively associated with health, particularly for older people. Building on this, we measure how indicators of attachment to place are associated with health for in people of advanced age in New Zealand. We use data from a cohort study (LiLACS NZ), which includes an indigenous Māori cohort aged 80–90 years and a non-Māori cohort aged 85 years from a mixed urban/rural region in New Zealand. Each cohort undertook a comprehensive interview and health assessment ( n = 267 Māori and n = 404 non-Māori). Using multivariate regression analyses, we explore participants' feelings for and connectedness with their home, community and neighbourhood; nature and the outdoors; expectations about and enthusiasm for residential mobility; and how all these are associated with measures of health (e.g., SF-12 physical and mental health related quality of life) and functional status (e.g., NEADL). We demonstrate that people in advanced age hold strong feelings of attachment to place. We also establish some positive associations between attachment to place and health in advanced age, and show how these differ for the indigenous and non-indigenous cohorts. For older Māori there were strong associations between various health measures and the importance of nature and the outdoors, and connectedness to neighbourhood and community. For older non-Māori, there were strong associations between health and liking home and neighbourhood, and feeling connected to their community and neighbourhood. Place attachment, and particularly its relationship to health, operates in different ways for different groups. Highlights: Attachment to place is positively associated with function and wellbeing in advanced age. Place attachment can be understood as both positive feelings and sense of connectedness. Place attachment can also be measured temporally, through plans and preferences for staying put. The health effects of place attachment are observed beyond home, at community or environment level. Associations between place attachment and health work differently for different ethnic groups.